Transforms and applications handbook - Poularikas, Alexander D., 1933- (Electrical engineering handbook series., 2010)
Highlighting the use of transforms and their properties, this title offers an introduction to signals and systems, including properties of the delta function and some classical orthogonal functions. It then details different transforms, including lapped, Mellin, wavelet, and Hartley varieties.